(untitled) (Numerus academy review, 2026)
The administrative judiciarystudies the case file broughtbeforeitafterfulfillinga set of formal and objective conditions. And thisresearchaims to studythese objective conditions and clarify the cases in whichthey are achievedsothat the administrative decisioncanbechallenged. These conditions have been reached, which are related to the validity of the externallegalityrelated to the administrative decision, whichis the presence of a defect in the element of competence and the element of form and procedures, and with regard to internalillegality, disadvantages of the administrative decisionrelating to itssubjectitis the element of reason, place and purpose, If the administrative decisioncontains one or more of these defects,this decision has become subject to contestation and cancellation by the competent administrative judiciary, which means that the administrative body issuing the decision must cancel itand award compensation whereappropriate.